(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
This study rigorously investigates the pedagogical and neurocognitive impacts of didactic games on reading comprehension, structural decoding, and longitudinal cognitive retention among early primary school students. Utilizing an expansive 12-week longitudinal quasi-experimental design (N=164), the research systematically evaluated targeted gamification typologies against standard, passive reading instruction frameworks. Quantitative results demonstrated a definitive 38.4% improvement in inferential reading speeds and a statistically significant 27.6% increase in complex narrative retention within the active experimental cohort (p < 0.001). The empirical data robustly confirms that structural, rule-based gamification intrinsically optimizes semantic decoding algorithms in the developing brain and securely sustains high-level cognitive engagement during complex linguistic tasks. Consequently, integrating specific, interactive didactic typologies into foundational primary reading curricula is strictly necessary to disrupt systemic pedagogical fatigue and maximize early literacy benchmarks globally.